An overview of viruses infecting Dioscorea yams in subSaharan Africa - Kenyon, L.; Shoyinka, S.A.; Hughes, J.; Odu, B. (2003)
Viruses of the genera Potyvirus, Potexvirus, Badnavirus, Cucumovirus, and Carlavirus infect yams of different species worldwide. These viruses cause a range of symptoms including mosaics, mottle, vein clearing, chlorosis, stunting, and distortion. These lead to a chronic and sometimes severe disease situation in all yam growing areas. In sub-Saharan Africa, where more than 90% of the world’s yams are produced, Yam mosaic virus (YMV), genus Potyvirus is an ubiquitous pathogen. It is the only wellcharacterized virus infecting yams. Other viruses infecting yams in sub-Saharan Africa are Dioscorea alata virus (DAV), genus Potyvirus; Dioscorea alata bacilliform virus (DaBV), genus Badnavirus; Cucumber mosaic virus (CMV), genus Cucumovirus; and Dioscorea dumetorum virus (DdV), genus Potyvirus. Dioscorea mottle virus (DMoV), a possible member of the genus Comovirus, was recently isolated from Dioscorea alata in Nigeria. Transmission studies show that YMV, DAV, DaBV, and CMV are mechanically transmissible between yam plants. All these viruses are transmitted by aphids, except DaBV, which is transmitted by mealybugs (Planococcus citri). Although tuber yield losses have been attributed to virus infection, the infl uence of these viruses on yield and growth of the yam plant has not been well studied. Tremendous improvement has been achieved in the detection of yam viruses with the development of highly sensitive and more specifi c diagnostic techniques such as enzyme-linked immunosorbent assays (ELISA), immunosorbent electron microscopy (ISEM), and polymerase chain reaction (PCR). The reliability of these diagnostic tools has enabled the production of virus-tested in-vitro germplasm which can be safely distributed internationally.